Analysis of Capitation Fund Management Mechanisms at Pratama Dental Clinics and Partner Dentists at Pratama Dental Clinics - Afriany, Leny; Wahyudi, Bayu; Sukajie, Bambang (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
The Primary Dentist functions as gatekeeper which provides services in first-level health facilities. Payments to primary dentists are set using a capitation system of IDR 3,000/per patient, varying at each health facility. This payment system requires dentists to manage utilization well and effectively. The research aims to analyze the allocation, utilization and transparency of primary dentist capitation funds. This research was conducted qualitatively using in-depth interviews, document review and observation. Research informants were selected randomly purposive sampling consisting of 2 partner practice dentists at Pratama Clinic and a Pratama Clinic dentist in Bandung City with high and low capitation coverage. It can be concluded that the distribution of participants to dentists in the city of Bandung is not evenly distributed so that there is still an inadequate allocation of capitation funds in acceptance which may have an impact on operations and service quality. Most of the operational costs are used for consumable medical materials. The suggestion from this research is that BPJS Health should adjust capitation norms, equalize the distribution of participants and clarify the regulations for dental and oral health services from the National Health Insurance. There is also a need for transparency in accepting capitation for dentists as the spearhead of services.